2014
DOI: 10.1111/cmi.12265
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of insect cells bySpiroplasma citriinvolves spiralin relocalization and lectin/glycoconjugate-type interactions

Abstract: SummarySpiroplamas are helical, cell wall-less bacteria belonging to the Class Mollicutes, a group of microorganisms phylogenetically related to low G+C, Gram-positive bacteria. Spiroplasma species are all found associated with arthropods and a few, including Spiroplasma citri are pathogenic to plant. Thus S. citri has the ability to colonize cells of two very distinct hosts, the plant and the insect vector. While spiroplasmal factors involved in transmission by the leafhopper Circulifer haematoceps have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 76 publications
0
34
0
Order By: Relevance
“…The most abundant membrane protein of S. citri , spiralin, has been verified to play a major role in the very early step of cell invasion (Duret et al . ). Phosphoglycerate kinase is a cytosolic protein on surface and research has shown that S. citri transmission by its insect vector is correlated with its ability to bind actin (Labroussaa et al .…”
Section: Introductionmentioning
confidence: 97%
“…The most abundant membrane protein of S. citri , spiralin, has been verified to play a major role in the very early step of cell invasion (Duret et al . ). Phosphoglycerate kinase is a cytosolic protein on surface and research has shown that S. citri transmission by its insect vector is correlated with its ability to bind actin (Labroussaa et al .…”
Section: Introductionmentioning
confidence: 97%
“…Phytoplasma mali” (Boonrod, Munteanu, Jarausch, Jarausch, & Krczal, ). And spiralin which is the richest membrane protein of Spiroplasma citri also takes a major role in the early phase of cell invasion (Duret et al, ). The surface protein P86 of S. citri has adhesive function when it infects with its host Circulifer tenellus (Yu, Wayadande, & Fletcher, ; glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH), pyruvate kinase and enolase are not only antigenic and membrane proteins, but also involved in adherence in Mycooplasma gallisepticum (Alvare, Blaylock, & Baseman, ; Chen et al, ; He et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Keywords: Biofilm; Endosymbionts; MBSP movement; Ultrastructure; Microvilli Phytoplasmas are obligated phytopathogenic bacteria living in both plants and insects depending on them for its acquisition and inoculation DURET et al, 2014). They are acquired by its vector passively during feeding on infected plants with consumption times being as short as few minutes but generally measured in hours (WEINTRAUB, 2007).…”
Section: Ultrastructure Studies Applied To the Movement Of Maize Bushmentioning
confidence: 99%
“…During this process, internalization of spiroplasmas into insect cells is an obligate step which requires intimate interactions, for both crossing the gut epithelium (acquisition) and invading the salivary gland cells (transmission) (DURET et al, 2014).…”
Section: Ultrastructure Studies Applied To the Movement Of Maize Bushmentioning
confidence: 99%
See 1 more Smart Citation